DEVELOPMENT OF DECISION SUPPORT SYSTEM DETERMINING THE STUDENT AS SCHOLARSHIP RECIPIENTS BY FUZZY MULTI ATTRIBUTE DECISION MAKING (FMADM) - Hoga Saragih; Murni Marbun; Bobby Reza (Faculty of Computer Science Universitas Indonesia, 2013)
This research is the design of a decision support system (DSS) to determining the student as scholarship recipients of the STMIK Pelita Nusantara, Medan, Indonesia, with the approach of Fuzzy Multi Attribute Decision Making (FMADM) with TOPSIS method. Approach to Fuzzy Multiple Attribute Decision Making (FMADM) by specifying the values of the weights for each of the criteria or attributes and TOPSIS method for selecting student scholarship recipients. Implementation of a decision support system that can show the interaction of the user with the software application built using Visual Basic 2008 programming language. Conclusion the results obtained from the discussion shows that the approach with FMADM TOPSIS give final value calculation results ordered that can help decision makers determine the student deserves the scholarship. The existence of a decision support system that has been designed so the process of determining a student scholarship recipients more accurately, quickly, and accurately.